Ethiopia - Two Microfinance Delivery Programs - Muntemba, Shimwaayi (World Bank, Washington, DC, 2012)
Formal financial institutions in Ethiopia have traditionally focused on the accessible urban towns leaving rural areas, where the majority of the population resides, without access to financial services. Recognizing this problem, a number of development agencies such as Redd Barna and World Vision started to provide access to financial services to the poor in rural areas in the 1980s. They undertook income generation programs by forming saving and credit schemes. Credit to the rural poor was provided in the form of grants, and agricultural inputs. Women were the primary targets of these programs. This study summarizes the findings of action research conducted on microfinance institutions in Ethiopia, with focus on the performance of Redd Barna and on Irish Aid-supported program. Action research facilitates the exchange of information on innovations and experiences so that other micro-finance institutions may learn from each other's mistakes and replicate best practices. The extended study on which this article is based addresses their mode of operation, organization, legal framework, as well as the financial and non-financial services they offer. The focus in on one urban and two rural and savings and credit schemes.